2015
DOI: 10.1007/s11277-015-2701-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Spectrum Sensing for the Cognitive Radios: Test Analysing Using Kalman Filter

Abstract: Nowadays, the spectrum becomes more crowded and to solve this problem we use the cognitive radio technology, cognitive radio is a promising technology used to improve of spectrum utilization. Among important functions of the cognitive radio is the spectrum sensing. Most of the research works on the spectrum sensing for the cognitive radio networks are considered in a fixed temporal state, they are ignored impact of the mobility of a secondary user. We interested in the concept of the spectrum sensing in realti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…This filter was first used to solve trajectory tracking problems in preparation of the Apollo flights. It has become an essential algorithm for the trajectory processing in modern radar systems and other engineering applications [18][19][20][21][22][23][24][25][26][27]. In this paper, the application of KF plays an indispensable role, which aims to reduce the measurement noise of the used sensors in the proposed prototype, and through it, we can stabilize the operation of system in order to make it more efficient.…”
Section: Kalman Filter Algorithmmentioning
confidence: 99%
“…This filter was first used to solve trajectory tracking problems in preparation of the Apollo flights. It has become an essential algorithm for the trajectory processing in modern radar systems and other engineering applications [18][19][20][21][22][23][24][25][26][27]. In this paper, the application of KF plays an indispensable role, which aims to reduce the measurement noise of the used sensors in the proposed prototype, and through it, we can stabilize the operation of system in order to make it more efficient.…”
Section: Kalman Filter Algorithmmentioning
confidence: 99%
“…H. Errachid Adardour et al in [12] proposed a novel technique to study the effect of mobility of secondary user on spectrum sensing of cognitive radio system in real-time environment. The study concluded that mobility causes an adverse negative effect on sensing performance of the network.…”
Section: Present State Of Researchmentioning
confidence: 99%
“…In this part, we interested on local spectrum sensing model as presented in [33]. The output of this method gives a decision value compared with  that represents the decision of the energy threshold; if it is above the threshold, then the sensing of the primary user is present.…”
Section: Energy Detectionmentioning
confidence: 99%
“…For this, the sensing metrics are presented such as the detection probability P d and false alarm probability P fa [18], [33], [34], [35], [36]:…”
Section: Energy Detectionmentioning
confidence: 99%